Recent snow cover changes over central European low mountain ranges. Issue 2 (17th October 2019) - Dong, Chunyu; Menzel, Lucas
Abstract: In this study, we simulated the snow water equivalent (SWE), rain‐on‐snow (ROS) events, evapotranspiration, and run‐off for the period 1961–2016 in a central European region covered by low mountain ranges (<820 m a.s.l.) using a distributed hydrological model TRAnspiration and INterception evaporation model (TRAIN). We utilized improved cloud‐free Moderate Resolution Imaging Spectroradiometer (MODIS) snow cover products to evaluate the modelled snow‐covered area, indicating a good performance of the snow modelling. We analysed the intra‐ and inter‐annual variations of the simulated hydrological variables and the synchronous climate variables (air temperature and precipitation). Trend detection indicates a significant SWE decline throughout the snow season, but principally at the high elevations; the most severe warming occurred in early spring (March), whereas precipitation showed a slight increase in January and February. The snowpack in February has displayed the most striking reduction during the past 56 years, which is likely related to both the highest susceptibility of snow to warming and the increased ROS occurrence in February since the early 1990s. The increased combination of high temperatures and extreme rainfalls, as well as the earlier snowmelt, has resulted in a run‐off increase during the earlier winter but a decrease in March. The expected changing climate towards warmer and wetter winters will probably exacerbate winter flooding in the future. Abstract : Response of snow water equivalent, rain‐on‐snow, evapotranspiration, and run‐off to climate change during 1961–2016 in a central European region was simulated. February displayed the most striking snow reduction and highest sensitivity to warming. Increased combination of high temperatures, extreme rainfalls, and earlier snowmelt has induced a run‐off increase in early winter, but a decrease in spring, which may exacerbate winter flooding and spring drought.